Postijni epiteti-kolʹoronazvi v ukraïnsʹkih dumah: priroda, estetika i poetika - Becenko, Tetâna (Stylistyka, 2002)
Clause is devoted to the versatile analysis of the folklore epithets used in texts of the Ukrainian dumas. The basic attention is concentrated, except for revealing essence of the named microstructures, on semantic-stylistic use of these expressive by way of the contents and figurative value of units, their aesthetic fullness.